PENGARUH MEDIA CERITA BERGAMBAR BERBASIS MIND MAPPING TERHADAP LITERASI BERBAHASA ANAK (Joyful Learning Journal, 2022)
The purpose of this study was to reveal and analyze the effect of mind mapping-based illustrated story media on language literacy in early childhood. The method used in this research is survey research with a quantitative research approach. The population in this study were 45 children in group B (TK Negeri 1 Rembang, TK Negeri 2 Rembang and TK Negeri Pembina Pamotan). The results showed that mind mapping-based pictorial story media had a positive and significant effect on children's language literacy. The description of the mind mapping-based illustrated story media shows good results. Likewise, the description of language literacy shows good results, and the correlation value of mind mapping-based illustrated story media on language literacy is in a strong position